IMPROVING THE PROCESS AND OUTCOMES OF SCIENCE LEARNING USING THE TALKING STICK LEARNING MODEL WITH WORDWALL MEDIA AT FOURTH GRADE STUDENTS AT SD NEGERI 130/II PASIR PUTIH - Novita, Ovra; Sundahry, Sundahry; Dani, Refril (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This research is motivated by the teaching and learning process not fully using learning models, the delivery of material is still monotonous, and teachers have not fully used learning media in social science learning, resulting in low social science learning outcomes in class IV SDN 130/II Pasir Putih. The aim of this research is to describe the improvement of the cognitive social science learning process and outcomes using the Talking Stick learning model with Wordwall media for class IV students at SD Negeri 130/II Pasir Putih. This research is classroom action research, consisting of two cycles. The research subjects were fourth grade students at SDN 130/II Pasir Putih. Research data was collected using qualitative and quantitative data analysis techniques. The research results show the process and results of class IV social science learning at SDN 130/II Pasir Putih. Details of teacher observation results in cycle I obtained a percentage of 76.91% in the good category and in cycle II obtained a percentage of 92.30% in the very good category. The results of student observations in cycle I obtained a percentage of 57.05% in the sufficient category and in cycle II obtained a percentage of 85.00% in the good category. Student learning outcomes in cycle I obtained a percentage of 35.00% with good/very good (complete) criteria totaling 7 students, in cycle II obtained a percentage of 75.00% with good/very good (complete) criteria totaling 15 students. It was concluded that the use of the Talking Stick model with Wordwall media could improve the science AS learning process and outcomes.